The search for lost Baltic personal names in Latvian surnames and old written texts - Siliņa-Piņķe, Renāte; Rapa, Sanda (Baltistica, 2025)
The aim of this article is to illustrate the method for the potential identification of Latvian pre-Christian personal names elaborated and approbated by the authors, considering that earlier research encourages a hypothesis that at least some contemporary Latvian surnames can be traced to ancient personal names of Baltic origin. The article introduces an approach that combines geographical, historical, linguistic, and statistical methods; hence, two examples have been illustrated in the analysis.Latvian surnames with suffixes -ān- and -ēn- (viewed as patronyms by researchers) and without a clear appellative or a newer forename have been selected. In the article, they are represented by such surnames as Beitāns/Beitēns and Geidāns. To the extent possible, we have identified the distribution of such anthroponyms in the territory of Latvia nowadays and in older documents. The distribution is then compared to corresponding Latvian toponyms of different ages. Lastly, possible etymologies are considered by comparing them to the research data on Lithuanian and Old Prussian personal names and by establishing other possibilities of origin from contact languages. Based on this analysis, conclusions are formed about the potential connection between selected surnames and the old personal names of ancient Balts.Among registered contemporary Latvian surnames, there are about ten surnames derived from the root Beit-. In the 1930s, the surname Beitāns was widespread in southern Latgale, Selonia, and eastern Vidzeme. There are also forms such as Beite, Beits in Selonia; Beitiņš in Zemgale, Vidzeme; Beitiks in Vidzeme. Documents from the 16th century feature a personal name with the root Beit- distributed sporadically all over Latvia. In Vidzeme, there were no personal names with the root Beit- in the 17th century; however, there are relatively many homestead names derived from the root in south-eastern and north-western parts of Vidzeme. Contemporary place names exhibit a similar distribution, and they are concentrated along the southern border of Latvia and in Vidzeme. Patronymic forms are quite dominant. When considering the distribution of the onomastic stem Beit-, its potential origin, unconvincing explanations of its origin, and toponymic evidence, it can be concluded that Beit- is, possibly, a stem of a Baltic personal name which was widespread in the 16th century and now remains in surnames and place names all over Latvia.There are also more than ten surnames registered in contemporary Latvia that are derived from the root Geid-/Ģeid-. In the 1930s in Latgale, surnames Geide, Geidāns, and Geiduks were widespread, and in Selonia – Geida, Geide, and Ģeida, also Geidāns and Ģeidāns. None of these surnames were widespread in Kurzeme and Semigallia, but in Vidzeme in 1826 the surnames Geide and Geidjan were registered in manor estate metrics; therefore, the root Geid-/Ģeid- can be mainly linked to southern and south-eastern parts of Latvia. Older proper names written with the root Geid- have been identified in Vidzeme metrics from 1638. Those are five homestead names, but there are no such personal names. A tendency geid- > gaid- has been identified in homestead names from later documents. Nowadays, homesteads named Geidāni are mostly concentrated in south-eastern Vidzeme, Latgale, and Selonia. Underived variants can also be established in northern Vidzeme, and Kurzeme. The Latgalian and Selonian surnames can be connected hypothetically with the Lithuanian and Polish languages. However, this etymology is not reliable because the sound shift ai > ei is only present in a small area of northern Latgale in Latvia. The onomastic root Geid-, according to its distribution in Latvia and its related etymologizations, is of the Baltic origin; however, it most likely entered the Latvian language through Lithuanian. Its etymology is assumed to be the Indo-European verb root *ghei̯dh- ‘wait’. When considering the results of the study, it may be concluded that the historical, geographic, and etymological methods allow the recovery of lost Baltic personal names, namely, to specify the origin of personal names, and to demonstrate the origin, distribution, and history of the productivity of the stem of the proper name.
Keywords: Latvian personal names; surnames; homestead names; reconstruction